Tecno-Legal Provisions for Safer High-rise Apartment Construction in Nepal - Mishra, Anjay Kumar; Aithal, PS (Journal of Advanced Research in Geo Sciences & Remote Sensing, 2021)
The paper aims to review the techno-legal provisions for safer high rise appartment construction in Nepal. The review of existing acts, rules, directives, guidelines, byelaws, codes and other unpublished documents were done for the research using content analysis followed by expert consultation as it needs to be viewed in different technical aspects which need expertise of different fields. The major provisions of the building code for seismic safety of apartment buildings are defined in Nepal National Building Code (NBC) 105:1994 and international codes are also used fulfilling the minimum requirements of the Nepal National Building Code as per NBC 000:1994. The architectural design parameters, fire fighting provisions, provisions of fire safety requirements are conformed as per the relevant NBC. At least eight government authorities are directly involved in the process of approval and building permit process. There is the provision of third party monitoring system also. Similarly the use approval to the earthquake damaged apartment is provided after repair, restore and retrofitting work according to the damage category and severity of the damages in structural and nonstructural members. For the effective compliance of the NBC and byelaws in apartments seismic safety of high rise buildings should be increased in NBC 105:1994 updating the seismic design parameters, building byelaws provisions should be updated for higher value of green open spaces, setbacks and access road. Effective coordination between all stakeholders and independent third party supervision and monitoring process should be done. For minimizing the issues raised by the neighbours after Gorkha Earthquake 2015, proper zoning for apartment construction, seismic vulnerability assessment of the existing apartments and Insurance of Neighbours of the apartments should be done. It is a review research to signify the role of NBC and bylaws for development of Nepal. How to cite this article:  Mishra AK, Aithal PS. Techno-Legal Provisions for Safer High-rise Apartment Construction in Nepal. J Adv Res Geo Sci Rem Sens 2021; 8(1): 16-46. DOI: https://doi.org/10.24321/2349.7661.202102